2010
DOI: 10.1007/s13280-010-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modern Forest Management on Winter Grazing Resources for Reindeer in Sweden

Abstract: Boreal forests in Sweden are exploited in a number of ways, including forestry and reindeer husbandry. In the winter, reindeer feed mainly on lichens, and lichen-rich forests are a key resource in the herding system. Commercial forestry has mainly negative effects on reindeer husbandry, and conflicts between these two industries have escalated over the last century. This article reviews the effects of modern forest management practices on the winter resources available for reindeer husbandry. Forestry affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 45 publications
1
63
0
1
Order By: Relevance
“…After the 1950s, selective cutting was replaced by clearcutting (all trees removed in a single harvest), followed by prescribed burning or scarification (topsoil turned over to expose mineral soil). Forestry activity has reduced both terricolous and arboreal lichens, and access of reindeer to pastures has been hampered as a result of tree cutting, site preparation, fertilization, and logging residues, as well as forest fragmentation caused by roads and ditches (Pruitt, 1979;Berg et al, 2008;Kivinen et al, 2010;Jaakkola et al, 2013). For example, in Kuukas the mean coverage of reindeer lichens in sub-xeric heath forests was 5.0% in the period 1976 -77 but only 0.6% in the years 2002 -04 (Mattila, 2006).…”
Section: Reasons For Feedingmentioning
confidence: 99%
“…After the 1950s, selective cutting was replaced by clearcutting (all trees removed in a single harvest), followed by prescribed burning or scarification (topsoil turned over to expose mineral soil). Forestry activity has reduced both terricolous and arboreal lichens, and access of reindeer to pastures has been hampered as a result of tree cutting, site preparation, fertilization, and logging residues, as well as forest fragmentation caused by roads and ditches (Pruitt, 1979;Berg et al, 2008;Kivinen et al, 2010;Jaakkola et al, 2013). For example, in Kuukas the mean coverage of reindeer lichens in sub-xeric heath forests was 5.0% in the period 1976 -77 but only 0.6% in the years 2002 -04 (Mattila, 2006).…”
Section: Reasons For Feedingmentioning
confidence: 99%
“…Further, the Swedish populations of ungulates, mainly elk (Alces alces) and roe-deer (Capreolus capreolus) increased substantially during the second half of the 20th century raising questions about monitoring of populations (Månsson et al 2011), browsing damages, and forage availability. Further, although reindeer (Rangifer tarandus) are domesti cated, improved information related to the interaction between reindeer herding and forestry (Kivinen 2010) was also asked for.…”
Section: In 2003 the Intergovernmental Panel On Climate Change (Ipcc)mentioning
confidence: 99%
“…In Kivinen et al (2010), the authors state "Ideal winter grazing areas have a high abundance of both ground growing and arboreal lichens that are easily accessible to reindeer". This is also true of the routes the reindeer travel in between their winter and summer grazing areas.…”
Section: Corridor Habitatmentioning
confidence: 99%
“…Forestry practices have drastically reduced the amount and accessibility of lichen in northern forests, and many studies have concluded that current forest practices have been detrimental to reindeer husbandry (Berg et al 2008, Kivinen et al 2010 Specifically, short rotations, soil scarification and dense stands negatively impact lichen presence and accessibility in the forest. Additionally, shortened rotations have reduced the amount of old growth forest in which arboreal lichen grows (Esseen et al 1996).…”
mentioning
confidence: 99%